Modeling Of Electrical Distribution Networks With Particle Swarm Optimization Technique For The Improvement Of Voltage Profile And Loss Reduction - Shahad, Falih Khlaif (UTeM, 2016)
Modeling of power distribution networks needs accurate impedance data of overhead lines and underground cables. In unbalanced distribution networks, the mutual and selfimpedances are required. The need of accurate impedance data is for evaluation electrical of distribution system planning with economic considerations. The data of series impedance is also used to investigate power flow in all segments in the distribution system. Therefore, modified Carson's equations have been utilized in this study to calculate series impedance of both overhead lines and underground cables using MATLAB program for getting more accurate results. MATLAB program has the ability to get the result of three phase, two phases, and single phase according to user's choice. The IEEE tests have been used to validate this work. Two tests, as the IEEE 34 bus test and IEEE 13 bus test are implemented. Determination of power flow was done using Open Distribution System Simulator (OpenDSS) program which is suitable for electrical distribution networks. The obtained results from OpenDSS program are used to find the optimum location and sizing of capacitors that would be installed in distribution system. The particle swarm optimization (PSO) is utilized to solve the problem of location and sizing of capacitor. Constraints of voltage profile and total demand of reactive power were considered. Installation of capacitors before and after optimization was compared based on voltage profile and reduction of power losses. The results of this work showed that the method for the calculations of the series impedance (series resistance and inductance) per unit of length is acceptable according to IEEE standard data. The method is accurate and has advantage as easy to implement which accomplished with Carson's equations. In addition, the results indicated that PSO algorithm has succeeded in finding proper placement and sizing of capacitor bank.